RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND THE OCCURRENCE OF OBESITY BASED ON BODY FAT PERCENTAGE IN ELDERLY AT GRIYA USIA LANJUT ST. YOSEF SURABAYA - Nanjong, Michael Salvatore; Wulandari, Yudita; Meryana, Pauline (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Background: The Central Statistics Agency released data showing that Indonesians aged ? 65 have increased by 25%, from 25 million in 2019 to 80 million in 2050. The growing elderly population can lead to health issues in the elderly, such as an increased risk of obesity. This health problem needs attention. Body Mass Index (BMI) is the most commonly used method to assess obesity, but it has shortcomings compared to skinfold calipers, which assess obesity based on fat mass. Objective: To determine the relationship between the level of physical activity divided into rare, occasional, and frequent categories and the occurrence of obesity measured by skinfold calipers in the elderly. Method: The research design is cross-sectional. The population in this study consists of elderly individuals at Griya Usia Lanjut St. Yosef Surabaya. The research sample includes elderly individuals at Griya Usia Lanjut St. Yosep Surabaya who meet the inclusion and exclusion criteria. The minimum required sample size for this study i